Collaborative Pre-Task Planning Processes and Second Language Task Performance. (December 2022) - Leeming, Paul; Aubrey, Scott; Lambert, Craig
Task-based language teaching research has investigated the impact of planning on task performance, but little has been reported on the processes that take place while planning is undertaken. This study builds on previous planning research by providing a detailed analysis of four Japanese university learners' collaborative pre-task planning (two dyads) and their performance on a subsequent second language (L2) oral monologue task that required them to express their opinions on a problem and propose a solution to it. Follow-up interviews incorporating stimulated recall were also conducted to gain insight into learners' perceptions. Results suggest that the note-taking strategies employed, the interpersonal dynamics of the pairs, the L2 proficiency of the participants, and the language of planning (first language [L1] or L2) resulted in important differences in these learners' planning processes and subsequent task performances. The results are discussed in terms of how pre-task planning processes might be optimized in teaching and research.